Remarkable Evolutionary Conservation of Antiobesity ADIPOSE/WDTC1 Homologs in Animals and Plants. Issue 1 (28th June 2017) - Ducos, Eric; Vergès, Valentin; Dugé de Bernonville, Thomas; Blanc, Nathalie; Giglioli-Guivarc'h, Nathalie; Dutilleul, Christelle
Abstract: Ducos et al. report that the farnesylated protein ASG2 is the Arabidopsis ortholog of human WDCT1, which controls fat accumulation. Both proteins harbor.. ASG2 (Altered Seed Germination 2) is a prenylated protein in Arabidopsis thaliana that participates to abscisic acid signaling and is proposed to act as a substrate adaptor for the DDB1 (DNA damage-binding protein 1)-CUL4 (Cullin 4) E3 ubiquitin ligase complex. ASG2 harbors WD40 and TetratricoPeptide Repeat (TPR) domains, and resembles the well-conserved animal gene called ADP (antiobesity factor ADIPOSE ) in fly and WDTC1 (WD40 and TPR 1) in humans. Loss of function of WDTC1 results in an increase in adipocytes, fat accumulation, and obesity. Antiadipogenic functions of WDTC1 involve regulation of fat-related gene transcription, notably through its binding to histone deacetylases (HDACs). Our sequence and phylogenetic analysis reveals that ASG2 belongs to the ADP/WDTC1 cluster. ASG2 and WDTC1 share a highly conserved organization that encompasses structural and functional motifs: seven WD40 domains and WD40 hotspot-related residues, three TPR protein–protein interaction domains, DDB1-binding elements [H-box and DWD (DDB1-binding WD40 protein)-box], and a prenylatable C-terminus. Furthermore, ASG2 involvement in fat metabolism was confirmed by reverse genetic approaches using asg2 knockout Arabidopsis plants. Under limited irradiance, asg2 mutants produce "obese" seeds characterized by increased weight, oil body density, and higher fatty acid contents. In addition, considering some ASG2- and WDTC1-peculiar properties, we show that the WDTC1 C-terminus is prenylated in vitro and HDAC-binding capability is conserved in ASG2, suggesting that the regulation mechanism and targets of ADP/WDTC1-like proteins may be conserved features. Our findings reveal the remarkable evolutionary conservation of the structure and the physiological role of ADIPOSE homologs in animals and plants.